Advanced Imaging to Phenotype Patients With a Systemic Right Ventricle. Issue 20 (16th October 2018) - Helsen, Frederik; Claus, Piet; Van De Bruaene, Alexander; Claessen, Guido; La Gerche, André; De Meester, Pieter; Claeys, Mathias; Gabriels, Charlien; Petit, Thibault; Santens, Béatrice; Troost, Els; Voigt, Jens‐Uwe; et al.
Abstract : Background: Reduced ventricular function and decreased exercise capacity are widespread in adults with complete transposition of the great arteries after atrial switch (TGA‐Mustard/Senning) and congenitally corrected TGA (ccTGA). Advanced imaging techniques may help to better phenotype these patients and evaluate exercise cardiac response. Methods and Results: Thirty‐three adults with a systemic right ventricle (70% TGA‐Mustard/Senning, 37±9 years of age, 24% female, 94% New York Heart Association class I‐II) underwent echocardiogram, cardiopulmonary exercise testing, and cardiovascular magnetic resonance imaging at rest and during a 4‐stage free‐breathing bicycle test. They were compared with 12 healthy controls (39±10 years of age, 25% female, all New York Heart Association class I). TGA‐Mustard/Senning patients had a higher global circumferential strain (−15.8±3.6 versus −11.2±5.2%, P =0.008) when compared with ccTGA, whereas global longitudinal strain and systemic right ventricle contractility during exercise were similar in both groups. Septal extracellular volume (ECV) in ccTGA was significantly higher than in TGA‐Mustard/Senning (30.2±2.0 versus 27.1±2.7%, P =0.005). During exercise, TGA‐Mustard/Senning had a fall in end‐diastolic volume and stroke volume (11% and 8%, respectively; both P ≤0.002), whereas ccTGA could increase their stroke volume in the same way as healthy controls. Because of a greater heart rate reserve in TGA‐Mustard/Senning ( P for interaction=0.010), cardiac index and peak oxygen uptake were similar between both patient groups. Conclusions: Caution should be exercised when evaluating pooled analyses of systemic right ventricle patients, given the differences in myocardial contraction pattern, septal extracellular volume, and the exercise response of TGA‐Mustard/Senning versus ccTGA patients. Longitudinal follow‐up will determine whether abnormal exercise cardiac response is a marker of earlier failure.